2023
DOI: 10.3390/pharmaceutics15020505
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Drug and Gene Delivery in Pediatric Brain Tumors’ Cancer Stem Cells: Current Knowledge and Future Perspectives

Abstract: Primary malignant brain tumors are the most common solid neoplasm in childhood. Despite recent advances, many children affected by aggressive or metastatic brain tumors still present poor prognosis, therefore the development of more effective therapies is urgent. Cancer stem cells (CSCs) have been discovered and isolated in both pediatric and adult patients with brain tumors (e.g., medulloblastoma, gliomas and ependymoma). CSCs are a small clonal population of cancer cells responsible for brain tumor initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Depending on the amount of CD66c expression, breast CSCs on treatment with CD66c Ab-conjugated rhodamine-labeled liposomes (CDRHOL) indicated selective and enhanced cellular absorption [182]. Researchers have demonstrated that nanoparticle-based curcumin delivery has enhanced its bioavailability and resulted in the eradication of CD133 + CSCs, thereby inhibiting the growth of brain tumors [183]. The overexpression of CD133 in CSCs of osteosarcoma has been targeted by the application of CD133 aptamers conjugated with salinomycin loaded PLGA nanoformulations [184].…”
Section: Application Of Nanotechnology In Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Depending on the amount of CD66c expression, breast CSCs on treatment with CD66c Ab-conjugated rhodamine-labeled liposomes (CDRHOL) indicated selective and enhanced cellular absorption [182]. Researchers have demonstrated that nanoparticle-based curcumin delivery has enhanced its bioavailability and resulted in the eradication of CD133 + CSCs, thereby inhibiting the growth of brain tumors [183]. The overexpression of CD133 in CSCs of osteosarcoma has been targeted by the application of CD133 aptamers conjugated with salinomycin loaded PLGA nanoformulations [184].…”
Section: Application Of Nanotechnology In Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…The microenvironments of CSCs are also considerable targets, since they provide suitable space for self-renewal and increased CSC chemical and radiological tolerance, which include vascularization, hypoxia, tumour-associated macrophages/fibroblasts, and the extracellular matrix [ 83 ]. The drug and gene delivery systems, such as nanoparticles, have also been extensively studied for enhancing targeting therapies for CSCs in paediatric CNS tumours [ 166 ]. In recent preliminary reports, controversial results were achieved for the same (class) medications in several common paediatric CNS tumours by different study groups.…”
Section: Clinical Significance Of Tumour Stem Cells In Tumours Of The...mentioning
confidence: 99%
“…Nanoparticles are particulate dispersions or solid particles with particle sizes in the range of 10-1000 nm. Nanocarriers can protect RNAi molecules from enzymatic degradation and immune recognition and have much higher transportation efficiency across the cell membrane than other carriers [20,21]. Various nanoparticles already in use for gene delivery in different insects include silica nanoparticles (SNs), layered double hydroxides (LDHs) nanoparticles, liposomes, solid lipid nanoparticles (SLNs), and polymer nanoparticles [22][23][24].…”
Section: Introductionmentioning
confidence: 99%